Release of a Platelet-Aggregating Substance (Adenosine Diphosphate) from Rabbit Blood Platelets Induced by Saline “Extract” of Tendons - Hovig, Torstein (Thrombosis and Haemostasis, 1963)
1. Blood platelet aggregation was induced by addition of saline “extract” of tendons to citrated PRP (aggregation time 50—60 seconds). The aggregates were sedimented by centrifugation, and aggregating activity was demonstrated in the supernatant (termed supernat. A) with an aggregation time of about 15 seconds.2. It was demonstrated that the activity of the supernatant was due to ADP released from the platelets.3. The conclusion is drawn that the aggregation reaction initiated by the tendon “extract” can be divided into two steps: 1. release of ADP from the platelets, 2. aggregation caused by released ADP.4. The observations are discussed in relation to the formation of platelet plugs in vivo.